An amorphous phase formation at palladium / silicon oxide (Pd/SiOx) interface through electron irradiation - electronic excitation process - Takeshi Nagase; Ryo Yamashita; Atsushi Yabuuchi; Jung-Goo Lee (AIP Advances, 2015)
A Pd-Si amorphous phase was formed at a palladium/silicon oxide (Pd/SiOx) interface at room temperature by electron irradiation at acceleration voltages ranging between 25 kV and 200 kV. Solid-state amorphization was stimulated without the electron knock-on effects. The total dose required for the solid-state amorphization decreases with decreasing acceleration voltage. This is the first report on electron irradiation induced metallic amorphous formation caused by the electronic excitation at metal/silicon oxide interface.